1979
DOI: 10.1002/bms.1200060209
|View full text |Cite
|
Sign up to set email alerts
|

Direct derivatization of sulphate esters for analysis by gas chromatography mass spectrometry

Abstract: Gas chromatography mass spectrometry has been used to study the reaction between a range of aromatic, alicyclic and aliphatic sulphate esters and three perfluoroacylating reagents, viz. trifluoroacetic, pentafluoropropionic and heptafluorobutyric anhydride. Aromatic sulphates were found to react readily, when treated with a 1 : 1 mixture of a perfluoroacid anhydride and dry ethyl acetate, to form the perfluoroester derivative of the parent phenol in quantitative yield. Non-aromatic sulphates, on the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Analyses of sulfated steroids after extraction and solvolysis have found high concentrations of DHEAS and pregnenolone sulfate in rodent and human brains [68; 69; 165; 327]. Recent studies that measure intact sulfated compounds without deconjugation [113; 124; 125; 126; 179; 180; 203] or a protocol incorporating a solid-phase extraction column purification step and simultaneous hydrolysis/derivatization with heptafluorobutyric anhydride [176; 218] have found neither DHEAS nor pregnenolone sulfate present in abundant quantities in rodent brains. For example, DHEAS was not detected in the brains of either Sprague-Dawley rats or Swiss mice (less than 0.3 ng/g) [176; 180].…”
Section: Relative Dhea(s) Concentrations In Brain Vs Plasma Vs Cmentioning
confidence: 99%
“…Analyses of sulfated steroids after extraction and solvolysis have found high concentrations of DHEAS and pregnenolone sulfate in rodent and human brains [68; 69; 165; 327]. Recent studies that measure intact sulfated compounds without deconjugation [113; 124; 125; 126; 179; 180; 203] or a protocol incorporating a solid-phase extraction column purification step and simultaneous hydrolysis/derivatization with heptafluorobutyric anhydride [176; 218] have found neither DHEAS nor pregnenolone sulfate present in abundant quantities in rodent brains. For example, DHEAS was not detected in the brains of either Sprague-Dawley rats or Swiss mice (less than 0.3 ng/g) [176; 180].…”
Section: Relative Dhea(s) Concentrations In Brain Vs Plasma Vs Cmentioning
confidence: 99%
“…Simultaneous hydrolysis/ derivatization of PREG-S and DHEA-S with HFBA was investigated. Touchstone and Dobbins (31) reported that some sulfated steroids can react with HFBA for their conversion into heptafluorobutyrates suitable for GC-MS analysis, and Murray and Baillie (32) showed that this single-step reaction was quantitative only in the case of aromatic sulfated steroids and steroids with a 3 ␤ -sulfoxy-⌬ 5 structure, such as PREG-S and DHEA-S. The potential usefulness of this reaction was of interest because of its simplicity and the selectivity of the hydrolysis/acylation reaction.…”
Section: Derivatization Reactionmentioning
confidence: 99%
“…However, the extraction methodologies used do not usually recover the hydrophilic sulfate and glucuronide conjugates of these acids. Extraction of the conjugates would have resulted in overestimation of the "free" fraction because derivatization for gas chromatography would lead to deconjugation (17). The presence of DOPAC conjugates in human urine was reported by O'Gorman et al (9) in patients receiving L-DOPA.…”
Section: Discussionmentioning
confidence: 97%